Argentum sensitized zinc oxide photoelectrode: Fabrication, characterization and application for photoelectrochemical water splitting / Siti Nur Haslinda Mohd Daud - Siti Nur Haslinda , Mohd Daud (2018)
Current research reports the fabrication, structural- and optical-characterizations of Argentum (Ag) sensitized Zinc Oxide (ZnO) photoelectrode and their performance in photoelectrochemical (PEC) water splitting application. The optimization of ZnO nanopillars had been successfully carried out and the plasmonic Ag nanoparticles was then subsequently hydrothermally sensitized on ZnO nanopillars through varied Ag+ ions reduction time and AgNO3 concentration. The structural- and optical-properties of all samples were systematically characterized by using several characterization tools. After that, all of the samples were tested for PEC water splitting and linear sweep voltammetry technique was conducted to study the current-voltage behaviour. Additionally, Nyquist plot and Mott-Schottky plot were conducted to probe the electronic properties and charge transfer. Ag nanoparticles sensitized ZnO nanopillars with 30 min Ag+ ions reduction period and 1 mM AgNO3 concentration exhibit the highest photocurrent density (with maximum photoconversion efficiency) which is almost 1.4 times higher than that of ZnO nanopillars. Mott-Schottky analysis indicated that all photoelectrodes exhibit n-type characteristic, where the flat band potential and charge carrier density for all photoelectrodes can be derived hereafter. Ag nanoparticles sensitized ZnO nanopillars with 30 min Ag+ ions reduction period and 1 mM AgNO3 concentration showed the smallest capacitive arc diameter, which indicated that Ag nanoparticles enhanced the electron mobility and reduced the charge-transfer resistance.